2006
DOI: 10.1099/vir.0.81936-0
|View full text |Cite
|
Sign up to set email alerts
|

Domains of tobacco mosaic virus movement protein essential for its membrane association

Abstract: A series of deletion mutants of tobacco mosaic virus movement protein (TMV-MP) was used to identify domains of the protein necessary for membrane association. A membrane fraction was isolated from tobacco BY-2 protoplasts infected with wild-type and mutant TMV that produce MP carrying a 3 aa deletion. Deletions that affected membrane association were clustered around the two major hydrophobic regions of MP that are predicted to be transmembrane. Deletions in other hydrophobic regions also reduced membrane asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 44 publications
2
37
0
3
Order By: Relevance
“…In the same manner, a (conservative) substitution of the equivalent Leu with Val or Ile resulted in improved TMV movement (Toth et al, 2002;Kawakami et al, 2003). In contrast, substitutions of the equivalent b1 residue abolished virus movement in TRV (this study), and in CPMV, Chinese wheat mosaic virus (CWMV) and Prunus necrotic ringspot virus (PNRSV), as well as tubule formation in CPMV (Bertens et al, 2000, Martínez-Gil et al, 2009Andika et al, 2013), whilst deletion of part of the b1 region prevented TMV movement (Fujiki et al, 2006).…”
Section: Mps Of the 30k Superfamilymentioning
confidence: 91%
See 1 more Smart Citation
“…In the same manner, a (conservative) substitution of the equivalent Leu with Val or Ile resulted in improved TMV movement (Toth et al, 2002;Kawakami et al, 2003). In contrast, substitutions of the equivalent b1 residue abolished virus movement in TRV (this study), and in CPMV, Chinese wheat mosaic virus (CWMV) and Prunus necrotic ringspot virus (PNRSV), as well as tubule formation in CPMV (Bertens et al, 2000, Martínez-Gil et al, 2009Andika et al, 2013), whilst deletion of part of the b1 region prevented TMV movement (Fujiki et al, 2006).…”
Section: Mps Of the 30k Superfamilymentioning
confidence: 91%
“…On the one hand, a series of experiments on TMV 30K concluded that it was most probably an integral membrane protein with two a-helical transmembrane segments (although a tight association with membranes without transmembrane domains could not be excluded; Brill et al, 2000;Fujiki et al, 2006). The two transmembrane segments correspond to the regions predicted as strands b1 and b6 in the study of Melcher (2000), which is the nomenclature followed in the present study.…”
Section: Mps Of the 30k Superfamilymentioning
confidence: 99%
“…MPs belong to different protein families with unique functional and structural characteristics. The most studied MP is p30 from the Tobacco mosaic virus, a 30-kDa RNA-binding protein (4) with two putative transmembrane (TM) segments (2) that has so far been considered an integral membrane protein (13,42). At an early stage of infection, p30 associates with the ER network (18,59).…”
mentioning
confidence: 99%
“…The MP is a hydrophobic protein that behaves like a membrane-integral or tightly membraneassociated protein in differential fractionation experiments and contains two predicted transmembrane domains Brill et al, 2000Brill et al, , 2004 involved in ER association (Fujiki et al, 2006). The association with microtubules depends on MP amino acids 1 to 213 required for MP function (Kahn et al, 1998;Boyko et al, 2000bBoyko et al, , 2000cBoyko et al, , 2002Kotlizky et al, 2001).…”
mentioning
confidence: 99%